Problem solving skill of students of senior high schools and Islamic high schools in Tegal Regency in solving the problem of PISA based on Polya’s stage - Ayu Arfiana; Ariyadi Wijaya (Jurnal Riset Pendidikan Matematika, 2018)
This study aimed to describe the students’ problem solving skill of senior high school and islamic high school in Tegal Regency in solving the problem of PISA based on Polya’s stage. The type of this study was a survey research with quantitative approach. The population was the students of senior high schools and islamic high schools in Tegal Regency. A sample of 389 students of grade X from 12 schools was estabilished using the stratified random sampling technique and cluster random sampling. The data were collected by using a test utilizing 12 PISA test items (reliability was 0.668). The Description of the data were analyzed using mean score, standard deviation, maximum and minimum score, and the percentage of correct answer. The results showed that the problem solving skill of senior high school and islamic high school students in Tegal Regency in solving the problem of PISA based on Polya’s stage was categorized as low. The indicators of the devising plan and looking back showed that the skill was in a very low category. Viewed from the indicator of carrying out a plan, their skill was in a medium category.